Floral Biology and Pollination Strategies of Selected Durio and Boschia (Malvaceae) in Sarawak - Ng, Win Seng (Universiti Malaysia Sarawak (UNIMAS), 2020)
Durio sensu lato (s. lat.) is a genus under the subfamily Helicterodeae within the family Malvaceae which comprise of about 33 species, distributed across tropical Southeast Asia with Borneo as its center of diversity. The objectives of this study were: to investigate the floral biology of Boschia griffithii, Durio graveolens, Durio kutejensis and Durio zibethinus; to investigate the breeding mechanism of B. griffithii, D. graveolens and D. kutejensis; and to determine the phylogenetic relationships among Durio s. lat. species in Sarawak based on DNA sequences of nuclear internal transcribed spacer (ITS) and plastid maturase K (matK) region. Durio zibethinus and D. graveolens flower between July and October but may start as early as April. Durio kutejensis flowers mainly between September and October while B. griffithii flowers throughout the year. Floral development of all four observed species was similar at their initial phase. At budbreak, the buds appeared as small protuberances (buds appeared on primary and secondary scaffold branches for D. graveolens, D. kutejensis and D. zibethinus while buds appeared on leaf axils for B. griffithii) with the scales enclosing the primordial floral organs. The volume and concentration of nectar for D. graveolens, D. kutejensis and D. zibethinus showed a similar trend which started low, slowly peaked but dropped and stopped while B. griffithii had similar trend in nectar concentration but showed no discernible trend in the volume. Results from pollination experiments showed D. graveolens and B. griffithii as partially self-incompatible (based on ISI) while D. zibethinus was self-incompatible. Assessment of self-compatibility based on fruit set placed B. griffithii, D. graveolens and D. zibethinus as Class 1, slightly self-incompatible. Two vertebrate taxa visited three species of Durio flowers. Individuals of dawn bat Eeonycteris spelaea were observed to visit D. graveolens, D. kutejensis and D. zibethinus while spiderhunter bird Arachnotera sp. was found to visit only D. kutejensis. Seven invertebrateiv taxa were observed as main floral visitors of the Durio spp. and B. griffithii studied: honeybee Apis sp. (Apidae), carpenter bee Xycolopa latipes (Hymenoptera), night wasp Vespa sp. (Vespidae), pollen beetle (Nitidulidae), cockroaches (Blattodea) and thrip (Thysanoptera). The phylogenetic trees showed two clades within Durio s. lat.: Durio s. str. and Boschia. All accessions of D. graveolens from Sabah and Sarawak are closely related to D. kutejensis. Three accessions of B. griffithii resulted from this study were grouped together with two accessions of B. griffithii which were sampled from Kalimantan and Singapore.